Sleep function: Toward elucidating an enigma. (August 2016) - Krueger, James M.; Frank, Marcos G.; Wisor, Jonathan P.; Roy, Sandip
Summary: Sleep function remains controversial. Individual perspectives frame the issue of sleep function differently. We briefly illustrate how sleep measurement and the evolution, tissue organization levels, molecular mechanisms, and regulation of sleep could influence one's view of sleep function. Then we discuss six viable theories of sleep function. Sleep serves host-defense mechanisms and conserves caloric expenditures, but these functions likely are opportunistic functions evolving later in evolution. That sleep replenishes brain energy stores and that sleep serves a glymphatic function by removing toxic byproducts of waking activity are attractive ideas, but lack extensive supporting experimental evidence. That sleep restores performance is experimentally demonstrated and has obvious evolutionary value. However, this hypothesis lacks experimentally verified mechanisms although ideas relating to this issue are presented. Finally, the ideas surrounding the broad hypothesis that sleep serves a connectivity/plasticity function are many and attractive. There is experimental evidence that connectivity changes with sleep, sleep loss, and with changing afferent input, and that those changes are linked to sleep regulatory mechanisms. In our view, this is the leading contender for the primordial function of sleep. However, much refinement of ideas and innovative experimental approaches are needed to clarify the sleep-connectivity relationship.